The Effect of Halal Label and Brand Image on Purchasing Decisions for Wardah Products - Gita Widyawati; Roswaty; Shafiera Lazuarni (Lembaga Riset, Publikasi dan Konsultasi JONHARIONO, 2023)
This study aims to determine whether there is an influence between the Halal Label and Brand Image on Wardah Product Purchasing Decisions (Case Study in Management Study Program Students, Faculty of Economics, UIGM Palembang). This type of research is descriptive quantitative. The sample consists of 226 students who are calculated using the Slovin formula. And taking the sampling technique using purposive sampling. The method used is multiple linear regression analysis through the support of the Statistical Product and Service Solution (SPSS) version 24 program. Based on the results of the t-test Halal Label (X1) and Brand Image (X2) have a respective significance level of 0.00 <0, 05, which means that the two variables influence the purchase decision. The calculation of the f test proves that all independent variables simultaneously have a significant level with a significance level of 0.00 <0.05.